Sustainable scheduling: Development and application of an integrated method combining NEH heuristic and life cycle assessment - Prado, Gabriel Bazalia Victal do; Silva, Daiane Vitória da; Christoforo, André Luis; Oliveira, José Augusto -de [UNESP]; Toso, Eli Angela Vitor; Silva, Diogo Aparecido Lopes (Taylor & Francis, 2021)
This paper has developed a model to perform more sustainable scheduling in manufacturing operations based on the combination of makespan, profit margin, and environmental impact indicators. A case study was designed to run the developed model in the production of automotive identification labels. The proposed model combined the NEH heuristics for a flow-shop production scheduling problem followed by the cradle-to-gate Life Cycle Assessment of the labels, in order to find scheduling solutions for minimising major environmental impacts and aggregate more value to the production flow. The main results showed that the proposed model was able to increase the company’s schedule performance. For the scenario analysis, two-hybrid heuristics were compared: NEHS-1 and NEHS-2, and both showed better schedule results than the classical NEH. However, the best results were presented by the NEHS-2, and it should be further improved with local search heuristics, in future research.
Keywords: eco-efficiency; identification labels; integrated heuristic; Life cycle management; sustainable scheduling